Nanostructured Coatings for Stone Protection: An Overview - Ruffolo, Silvestro Antonio; La Russa, Mauro Francesco (Frontiers in Materials, 2019)
The protection of the stone materials represents an ongoing challenge in the field of conservation of cultural heritage. Protective coatings are used to make the stone more resistant against pollutants, biological growths and especially against the action of water. In last decades, nanoparticles were synthetized and tested to improve the performance of such coatings. In this review, two main enhanced coatings are reported: superhydrophobic coatings and photocatalytic coatings. The first ones have a very low adhesion, so dirty, pollutants and colonies of microorganisms can be easily “washed out” by the water. Photocatalytic coatings are able to oxidize organic matter on their surface, thanks to the combination of light and photocatalyst. The state-of-art of both technologies are discussed with advantages and drawbacks.